Is nickel hydroxide charging only skin-deep? - Hadden,JHL; Ryan,MP; Riley,DJ (ACS Applied Energy Materials, 2020)
The depth of charging in Ni(OH)2-coated electrodes treated with paraffin wax to remove porosity has been investigated using time-of-flight secondary-ion mass spectrometry after charging and discharging in deuterated solvent at pH 14. The proportion of deuterium uptake was found to be dependent on the number of charge/discharge cycles, showing that the measured deuterium signal was indeed dependent on the electrochemical redox activity of the sample. Sputter craters were characterized using atomic force microscopy to find the sputter rate. This then allowed the maximum depth of charging to be found to be approximately 20 nm. This confirmed a surface “skin” in which charging occurs with the rest of the bulk inactive.